Optimizing the Empowerment of Productive Waqf to Improve the Quality of Education and Teachers’ Welfare in Islamic Boarding Schools in Banten Province - Asep Furqonuddin; Kholid Kholid; Wasehudin Wasehudin; Aan Ansori; Iwan Kosasih (International Journal of Nusantara Islam, 2026)
This study aims to analyze the factors influencing healthcare workers’ compliance with safe injection procedures, focusing on knowledge, attitude, facility availability, and supervision. A quantitative, cross-sectional research method was employed, involving healthcare workers from selected healthcare facilities. Data were collected using structured questionnaires and analyzed through inferential statistical tests to identify relationships between variables. The findings revealed that knowledge, attitude, facility availability, and supervision significantly affect healthcare workers’ compliance. The discussion highlights that a combination of internal factors (knowledge and attitude) and external factors (facilities and supervision) forms the foundation of compliance behavior. In conclusion, improving safe injection practices requires comprehensive interventions that encompass competency enhancement, adequate facility provision, and strengthened supervision systems. The study’s contribution lies in providing empirical evidence to inform patient safety policy formulation at both facility and national levels.